Respuesta :
Hello,
sin (a+b)= sin a cos b+ cos a sin b
0=sin t cos3t +cos t sin 3t=sin (4t)
==>4t=kπ
==>t=kπ/4
sin (a+b)= sin a cos b+ cos a sin b
0=sin t cos3t +cos t sin 3t=sin (4t)
==>4t=kπ
==>t=kπ/4
we are given the equation sin θ cos 3θ + cos θ sin 3θ = 0 and is asked to simplify the given. In this case, we can use the summation in trigonometric identities to simplify the equation. this form is equivalent to sin (A+B) = sin A cos B + cos A sin B. This means the simplification is equal to sin 4θ